Prognostic study for isolated local recurrence operated with salvage excision in hormone-receptor-positive patients with invasive breast cancer after primary breast surgery - Chi-Chang Yu; Wen-Lin Kuo; Shih-Che Shen; Hsu-Huan Chou; Yung-Feng Lo; Ming-Chin Yu; Shin-Cheh Chen (Biomedical Journal, 2020)
Background: This study aimed to identify the factors that predict distant recurrence and survival outcome after patients with primary positive hormone receptor-positive (HR+) invasive breast cancer undergo complete excision for isolated local recurrence (ILR). Methods: From January 2000 to December 2009, we performed a retrospective review of our database and identified 51 patients with HR + invasive breast cancer who underwent complete excision for ILR as a component of salvage therapy. The distant metastasis-free survival (DMFS) and overall survival (OS) from the time of ILR were calculated using the Kaplan–Meier method, and a Cox regression model was used for multivariate analysis. Results: Of the 51 cases of ILR, 28 were of ipsilateral breast tumor recurrence and 23 were of chest wall recurrence. By receiver operating characteristic curve analyses, the cut-off time point for time to ILR was determined to be 29 months. According to time to ILR (≤29 vs. >29 months) and primary tumor size (≤2 vs. >2 cm), patients were divided into four risk groups as variables for analysis. On multivariate analysis, two independent prognostic factors for DMFS and OS after ILR were identified: risk groups (ILR≤29 months with primary tumor size >2 cm vs. ILR>29 months with primary tumor size ≤ 2 cm, HR = 8.53 for DMFS and HR = 11.18 for OS) and primary tumor grade (2/3 vs. 1, HR = 6.10 for DMFS and 4.27 for OS). Conclusion: We demonstrated that poor DMFS and OS are associated with high risk group defined as short time to ILR (≤29 months) with primary tumor size (>2 cm) and higher primary tumor grade (2/3) among patients with HR + invasive breast cancer treated with complete excision for ILR. Therapeutic strategies for ILR based on hormone therapy with new agents should be explored in future prospective studies, especially for patients with poor outcome. Keywords: Breast cancer, Excision, Hormone receptor-positive, Isolated local recurrence, Prognosis